Investigation of the role of miRNA variants in neurodegenerative brain diseases - Frydas, Alexandros; Cacace, Rita; van der Zee, Julie; Van Broeckhoven, Christine; Wauters, Eline (Frontiers in Genetics, 2025)
IntroductionmiRNAs are small noncoding elements known to regulate different molecular processes, including developmental and executive functions in the brain. Dysregulation of miRNAs could contribute to brain neurodegeneration, as suggested by miRNA profiling studies of individuals suffering from neurodegenerative brain diseases (NBDs). Here, we report rare miRNA variants in patients with Alzheimer’s dementia (AD) and frontotemporal dementia (FTD).MethodsWe initially used whole exome sequencing data in a subset of FTD patients (n = 209) from Flanders-Belgium. We then performed targeted resequencing of variant-harboring miRNAs in an additional subset of FTD patients (n = 126) and control individuals (n = 426). Lastly, we sequenced the MIR885 locus in a Flanders-Belgian AD cohort (n = 947) and a total number of n = 755 controls.ResultsWES identified rare seed variants in MIR656, MIR423, MIR122 and MIR885 in FTD patients. Most of these miRNAs bind to FTD-associated genes, implicated in different biological pathways. Additionally, some miRNA variants create novel binding sites for genes associated with FTD. Sequencing of the MIR885 locus in the AD cohort initially showed a significant enrichment of MIR885 variants in AD patients compared to controls (SKAT-O, p-value = 0.026). Genetic association was not maintained when we included sex and APOE status as covariates. Using the miRVaS prediction tool, variants rs897551430 and rs993255773 appeared to evoke significant structural changes in the primary miRNA. These variants are also predicted to strongly downregulate mature miR885 levels, in line with what is reported for MIR885 in the context of AD.DiscussionFunctional investigation of miRNAs/variants described in this study could propose novel miRNA-mediated molecular cascades in FTD and AD pathogenicity. Furthermore, we believe that the genetic evidence presented here suggests a role for MIR885 in molecular mechanisms involved in AD and warrants genetic follow-up in larger cohorts to explore this hypothesis.